2017
DOI: 10.1086/691210
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Approaches to Archaeological Fire Features and Their Behavioral Relevance

Abstract: The uses and functions of fire in early human adaptations are commonly debated and at times very controversial topics. It is important to recognize under what circumstances and conditions specific fire-related traces can be produced and preserved in the archaeological record. Currently, a growing body of data is emerging on the application of experimental research to the study of archaeological hearths and their residues. In this review, I draw together aspects of such available experimental data, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 93 publications
2
37
0
3
Order By: Relevance
“…The micro-FTIR results show mixed signals for the clays, with both heated and nonheated clays present. This mixing is not surprising, as experimental studies show that in an open fire, heating of the sediments below the fire rapidly diminishes with depth (e.g., Aldeias et al, 2017;Canti & Linford, 2000). Our results are in line with these experimental observations, as they show a decrease in heating traces within the same clay aggregate.…”
Section: Combustion Features and Clay Surfacessupporting
confidence: 91%
“…The micro-FTIR results show mixed signals for the clays, with both heated and nonheated clays present. This mixing is not surprising, as experimental studies show that in an open fire, heating of the sediments below the fire rapidly diminishes with depth (e.g., Aldeias et al, 2017;Canti & Linford, 2000). Our results are in line with these experimental observations, as they show a decrease in heating traces within the same clay aggregate.…”
Section: Combustion Features and Clay Surfacessupporting
confidence: 91%
“…Nonetheless, even if direct evidence for fire may be have been removed, there should be indirect evidence due to the effects that heat has on lithics, bones, and even the sediment, and all of these should remain (Aldeias 2017). When flint is exposed to heat, color changes can be visible at temperatures starting at 2507C, a distinctive luster begins to develop at temperatures of approximately 3507C, and crazing can occur starting at 3207C (Julig et al 1999:838 and citations within;Rottländer 1983).…”
Section: How Good Are These Data?mentioning
confidence: 99%
“…These effects are not limited to objects that are actually in the fire. A series of actualistic experiments (Sievers and Wadley 2008;Stiner et al 1995;Werts and Jahren 2007), as well as more highly controlled ones (Aldeias 2017;Aldeias et al 2016), has suggested that the heat from fires can transfer to underlying sediments, though exactly how far down and the rate of transfer are dependent on several variables. For example, figure 1 below shows the results of two heat experiments at two different temperatures (9507C and 6007C) at the ground surface, with additional temperature readings at depths of 2, 6, 10, and 20 cm.…”
Section: How Good Are These Data?mentioning
confidence: 99%
See 1 more Smart Citation
“…All may be explained as geomorphologically or geochemically produced features, or products of interaction between the excavation process and site topography.^Even what Sorensen (2017a:121) cites as Bfire-reddened bedrock^under layer 55 at Combe Grenal is problematic. While rubefication of underlying substrates (sediments or bedrock) can be the result of exposure to heat (Aldeias 2017;Aldeias et al 2016), this is not the only possible cause. In fact, similar features on the bedrock floor at Pech IV, what we initially assumed to be hearth locations, turned out to be the result of the diagenesis and alteration of organic matter that had nothing to do with heating by fire (Goldberg et al 2018:25).…”
Section: How Well Does the Evidence Hold Up At Other Sites?mentioning
confidence: 99%